El espacio vivido: Experiencia sensorial en la obra de Rogelio Salmona en la Bogotá del siglo XX (2024)
Architecture has been in contact with the human being, managing to interpret political, social and cultural connotations, managing to interact directly with experiences and emotions. It contemplates the immediate natural and urban environment, generating positive or negative experiences that give importance to the stimuli and senses of those who inhabit it, it can influence the moods and activities that are carried out in it. In this way you can stimulate the being through experience, transmitting the feeling of not only knowing or observing the place but also, feeling part of it.